SrTiO3 Nanokubus: Sintesis, Kontrol Morfologi dan Sifat Termoelektrik (Tinjauan) - Yulia Eka Putri; Ratesha Najela; Nova Andriani; Diana Vanda Wellia (Akta Kimia Indonesia, 2021)
Thermoelectrics (TE), enabling the conversion of heat energy into electricity directly, provide the opportunity as alternative energy for conventional power generator with high efficiency. To date, bulk SrTiO3 nanocubes is the most promising oxide-based TE materials candidate. The nanoarchitecture of 3-dimensional SrTiO3 nanocubes (3D-STO) is the main target in realizing high performance TE materials with high ZT value comparable to commercially available telluride-based compound. The proper synthesis method is needed to form SrTiO3 with uniform nano-sized cubic particles. Liquid synthesis technique namely hydrothermal and solvothermal, succeeded in forming 20 nm of SrTiO3 nanocubes with high crystallinity and homogeneous morphology